Incorporation of lanthanide (Eu3+) ions in ZnS semiconductor quantum dots with a trapped-dopant model and their photoluminescence spectroscopy study. (25th August 2015) - Wang, Yongbo; Liang, Xuhua; Liu, Enzhou; Hu, Xiaoyun; Fan, Jun
Abstract: Doping quantum dots (QDs) with lanthanide (Ln) ions is promising to modify the optical properties of QDs, but incorporating Ln 3+ ions into QD hosts remains a challenge. In this work, we adopt the trapped-dopant model for fabricating Eu-doped ZnS QDs via direct wet chemical synthesis. Sharp Eu dopant photoluminescence (PL) was observed in the PL spectra of the as-prepared Eu-doped ZnS QDs and the bands at ∼590, ∼618 and ∼695 nm were assigned to transitions from 5 D0 to 7 F1, 7 F2 and 7 F4, respectively. Quenching of the ZnS bandgap PL and enhancement of the Eu dopant PL were observed with increasing Eu 3+ doping concentration, and also, the excitation spectra for Eu emission (618 nm) were similar to the typical excitonic features of the ZnS host. These spectroscopic results, as well as the XRD and EDS data, demonstrated that Eu 3+ ions were incorporated in the ZnS host rather than just on the surface, and the Eu dopant PL was derived from energy transfer from the QD host to Eu 3+ rather than direct excitation of Eu 3+ . By surface passivation, the sharp Eu emission was well-separated from the ZnS bandgap emission, which led to a good signal-to-noise ratio for more sensitive detection.